Rapid Screening of Free Oligosaccharides in Human and Animal Milks by HILIC-MS/MS and Tandem Mass Spectral Library (P13-033-19). (13th June 2019) - Remoroza, Concepcion; Liang, Yuxue; Mak, Tytus; Power, Michael; Stein, Stephen
Abstract: Objectives: Mammalian milk oligosaccharides (MMOs) from human and farm animals have been of great interest because of their functional application in food nutrition. However, the biological significance of the variation in proportions of MMOs among milks is poorly understood. MMO concentration (0.05 - 0.3 g/L) in mature animal milk is >20 fold lower than human milk oligosaccharides (HMOs) (12 g/L) [1]. Hence, screening techniques are necessary for the structural characterization of MMOs in milk. This study characterizes and compares chemical structures derived from tandem mass spectra of free oligosaccharides in the milk of human and animals for the development of a MS library for MMOs. Methods: Isolation and purification of MMOs by HILIC-MS analysis as described [1]. Precursor and product ion tolerances were <10 ppm when searched against the NIST 17 Tandem MS reference library coupled with the recently released HMO library using the NIST MS Search v2.3 software. These were used to annotate unknown precursor mass using peak areas of the free and annotated MMO in the milk of human, bovine, goat, buffalo and African lion. Results: A variety of unknown oligosaccharides were derived from results of HILIC-MS analysis of various milks. This comparative study of MMO composition resulted in the identification of 144 MMOs, of which 74 are derived from human milk. The number of identified compounds in the milk of lion (60) were different than those in other mammals; human, bovine (21), buffalo (43) and goat (44). MS/MS analysis of sialylated MMOs distinguished Neu5Gc from Neu5Ac. The mass spectral matching technique efficiently identifies MMO structures. Novel MMOs in milk samples were identified. African lion and buffalo milk had the fewest number of MMOs similar to HMOs. Note that type II linkage Gal(β1–4) is primarily found in animal milk compared with type I Gal(β1–3), typical in HMOs. [1] J. British Nutrition, Albrecht et al., 2014 [2] J. Analytical Chemistry, Remoroza et al., 2018 Conclusions: Detailed analysis of the chemical structures identified in this study documents significant variability of MMOs in milk of animals with respect to human milk. Funding Sources: NIST.